Advancing migration and health research by examining return migration - Serrano-Gallardo, P.; Mas-Giralt, R.; Castellani, S.; Juarez, S. P. (Journal of Epidemiology and Community Health, 2024)
This essay offers an analysis of research on return migration and health by adopting the social determinants of health (SDH) framework proposed by the WHO. Specifically, we argue that the SDH are implicated in the decision to migrate, stay or return, which in itself also contributes to social health inequities. Most theoretical frameworks developed to study migration have predominantly considered primary migration movements. The lack of a fluid consideration of the migration phenomenon has a direct impact on our understanding of the relationship between migration and health. In this essay, we, first, address the challenges of defining and studying return and its implications for health research. Second, we propose to use the WHO's SDH framework to understand how social factors shape migrants' health, influence the decision to return and can contribute to health inequalities. The conceptual approach developed in this paper can help design future studies on the health of return migrants, fostering interdisciplinary collaborations to investigate how social factors are embodied, giving rise to health inequities in society that are intricately linked to the migration experience.